Exploring The Alignment Between Teaching Activities and Curicullar Goal: A Perspective from Merdeka Curriculum - Nur Alfiani Ismail; Andi Muliati M; Chairil Anwar Korompot (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This research aims to explore the alignment between teaching activities and curriculum objectives in the context of Merdeka Curriculum. The Merdeka Curriculum, implemented in Indonesia, provides teachers with the flexibility to adapt the learning process to the needs of students, but also demands a clear alignment between the learning activities carried out and the achievement of curriculum goals. This research uses a qualitative approach with a case study method at SMPN 40 MAKASSAR which has implemented the Merdeka Curriculum. Data were collected through interviews with teachers, direct observation of learning activities, and interviews with several students. The results showed that teachers have tried to adapt teaching activities to the curriculum objectives, there are challenges in terms of a uniform understanding of curriculum implementation and the implementation of more contextualized learning activities. In addition, the alignment between teaching activities and curriculum goals is also influenced by factors such as teacher training, available resources and support from school management. This study suggests the importance of increased training and more continuous support for educators in order to achieve better alignment between teaching activities and curriculum objectives under Merdeka Curriculum.Keywords: teaching activities, curriculum goals, merdeka curriculum.